AVERAGING IN VARIOUS COMPUTING METHODS - Valko, H.B. (Journal of Information Technologies in Education (ITE), 2010)
In work the role of the weighed averaging in various computing methods is shown. Communication between methods by means of the weighed averaging is shown.